ESC PWM Fullbridge Motor DC Berbasis Arduino - jati, budi pramono; Hapsari, Jenny Putri (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
The problem with DC motors is speed regulation, adjusted to the needs in the field. The speed of a DC motor can be changed by adjusting the motor voltage. To overcome this, the motor voltage is regulated using Pulse Wide Modulation (PWM). PWM works by changing the duty cycle of the voltage in the form of pulses so that the average voltage can be changed. The solution is to use an Electronic Speed Control (ESC) controller where the pulse voltage duty cycle is realized using a variable PWM generator using an Arduino which is fed to a fullbridge MOSFET inverter. This paper discusses a DC motor ESC using PWM with a full bridge which is used for the inverter process, the aim is to prove the effect of voltage changes on the speed of a DC motor. The model is specified as a DC motor controlled with a fullbridge PWM inverter. PWM ESC consists of three main parts, namely AC to DC converter, fullbridge mosfet inverter, PWM variable signal source. The parameters determined are: change in duty cycle of the square wave signal. The method used is fullbridge PWM in the form of manufacturing design (hardware and software) and testing of DC motor speed controllers with PWM. The ESC parts consist of: fullbridge switching inverter, PWM signal generator, Arduino, Arduino sketch software, SMPS power supply. The ESC is built using 8 130A 200V MOSFETs, with a duty cycle varying from 0 -100%.